Successful Endoscopic Ethanol Injection and Clipping Treatment of Ruptured Duodenal Varices - Abayli, Bahri; Simsek, Yeliz; Avci, Begum Seyda; Kuvvetli, Adnan; Avci, Akkan; Erhan, Cigdem (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Abayli B, Simsek Y, Avci BS, Kuvvetli A, Avci A, Erhan C. Successful endoscopic ethanol injection and clipping treatment of ruptured duodenal varices. Turk J Gastroenterol. Published online November 21, 2025. doi:10.5152/tjg.2025.25502.